Corrosion and protection of galvanized steel in vegetation‐growing concrete (II): Coating protection. Issue 6 (13th September 2021) - Xiong, Shiyuan; Huang, Xiaole; Xu, Wennian; Guo, Xiaoping; Liu, Shuan
Abstract: In previous work, the corrosion performance and anti‐corrosion mechanism of galvanized steel wire embedded in vegetation‐growing concrete under marine environment was highlighted. In this work, a graphene‐modified epoxy coating was developed and applied to the protection of galvanized steel in vegetation‐growing concrete under a marine environment. The effect of dispersed graphene on the anticorrosion performance of the epoxy coatings was evaluated. The composite coatings displayed outstanding barrier properties against H2 O molecules compared to the pure epoxy coating. Salt spray test results revealed superior corrosion resistance offered by the prepared graphene‐modified epoxy coating on galvanized steel.